The Power of Narration in Online Media to Support the Sustainability of Maos Batik - Hartanti, Monica; Claudia Lukman, Christine (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research showed that historical events could create a narrative on batik motifs. The chronicle of the Javanese War had always been a part of the origins of Banyumasan Batik, including Maos Batik. The narrative about the Diponegoro War code on Maos Batik was a success factor in increasing the uniqueness of the Maos Batik. Although the truth was uncertain, this narrative was published and popularized through trusted online news media. The research used narrative analysis with a qualitative descriptive approach. Narrative data were collected through reliable sources, narrative analysis from Propp, and the semiotics of the Barthes signification system to reveal the myths and ideologies contained in the Maos Batik motif. Online questionnaire data was from 108 respondents to determine the respondent interest level after knowing the Batik motif's narrative as the code for the Diponegoro War. The research reveals that the narrative of the Maos Batik motif as a code for the Diponegoro War cannot be clarified the truth of its history. However, the socialization carried out by the company owners through the popularity of the leading online news media has made this narrative considered historical truth. Strengthened by the myths contained in the Maos Batik motif, it can function to naturalize history. If this is not considered a historical fact, then the narrative can be accepted as a marketing strategy. The dissemination of the narrative in Maos Batik through trusted online news media can enhance the uniqueness of Maos Batik, which becomes a differentiation from other regions. This attracts consumers to buy and supports sustainability of Maos Batik.Â